European Higher Education Area: The Impact of Past and Future Policies - Curaj, Adrian; Deca, Ligia; Pricopie, Remus (Springer Nature, 2018)
This volume presents the major outcomes of the third edition of the Future of Higher Education - Bologna Process Researchers Conference (FOHE-BPRC 3) which was held on 27-29 November 2017. It acknowledges the importance of a continued dialogue between researchers and decision-makers and benefits from the experience already acquired, this way enabling the higher education community to bring its input into the 2018-2020 European Higher Education Area (EHEA) priorities. The Future of Higher Education - Bologna Process Researchers Conference (FOHE-BPRC) has already established itself as a landmark in the European higher education environment. The two previous editions (17-19 October 2011, 24-26 November 2014), with approximately 200 European and international participants each, covering more than 50 countries each, were organized prior to the Ministerial Conferences, thus encouraging a consistent dialogue between researchers and policy makers. The main conclusions of the FOHE Conferences were presented at the EHEA Ministerial Conferences (2012 and 2015), in order to make the voice of researchers better heard by European policy and decision makers. This volume is dedicated to continuing the collection of evidence and research-based policymaking and further narrowing the gap between policy and research within the EHEA and broader global contexts. It aims to identify the research areas that require more attention prior to the anniversary 2020 EHEA Ministerial Conference, with an emphasis on the new issues on rise in the academic and educational community. This book gives a platform for discussion on key issues between researchers, various direct higher education actors, decision-makers, and the wider public. This book is published under an open access CC BY license.